2007
DOI: 10.4049/jimmunol.179.2.1147
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of the TLR5 Activation Domain Hampers Protective Potential of Flagellin DNA Vaccine

Abstract: Flagellin is a key component of the flagella of many pathogens, including Pseudomonas aeruginosa. Flagellin is an attractive vaccine candidate because it is readily produced and manipulated as a recombinant protein and has intrinsic adjuvant activity mediated through TLR5. Although DNA vaccines encoding native Pseudomonas B-type (FliC) or A-type (FlaA) flagellin are strongly immunogenic, the resultant Ab response interferes with the interaction of homologous flagellin with TLR5. This reduces the ability of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
41
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 44 publications
(37 reference statements)
3
41
2
Order By: Relevance
“…Therefore, in vivo blockade of TLR signaling by MAMP-specific neutralization Abs is a novel mechanism for down-regulating innate immunity. Our results are consistent with the report by Saha et al (31), which suggested that ex vivo Ab blockade of the TLR5 activation motif of Pseudomonas aeruginosa flagellin reduces its efficacy to induce lung innate responses. Interestingly, we found that neutralizing epitopes in S. typhimurium FliC are embedded within the conserved region (regions 1-173 and 401-494) that also carries the activation motif 89 -96 (8, 9).…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, in vivo blockade of TLR signaling by MAMP-specific neutralization Abs is a novel mechanism for down-regulating innate immunity. Our results are consistent with the report by Saha et al (31), which suggested that ex vivo Ab blockade of the TLR5 activation motif of Pseudomonas aeruginosa flagellin reduces its efficacy to induce lung innate responses. Interestingly, we found that neutralizing epitopes in S. typhimurium FliC are embedded within the conserved region (regions 1-173 and 401-494) that also carries the activation motif 89 -96 (8, 9).…”
Section: Discussionsupporting
confidence: 83%
“…The titers of flagellin-, OprI-, and OprF-specific IgG antibodies following immunization with OprF 311-341 -OprI-flagellins are in most cases two logs higher than those reported in other studies (12,14,22,50,51,67,68,70). For example, von Specht et al (62) required three immunizations with 70-fold more antigen to achieve equivalent antibody responses.…”
Section: Discussioncontrasting
confidence: 39%
“…aeruginosa possesses two types of flagellins, type A and type B, that differ in amino acid composition and length of the hypervariable region. P. aeruginosa flagellins have the unique property of being potent adjuvants as well as protective antigens (8,32,42,50). Previous work has established flagellin as a potent adjuvant in mice (1, 3, 9, 10, 23, 33-35, 45, 53, 56) as well as cynomolgus and African green monkeys (24,36).…”
mentioning
confidence: 99%
“…In a rat model of P. aeruginosa-induced pneumonia, administration of human monoclonal antibodies (MAbs) to flagella provided protection against infection and decreased lung injury (24), and another set of human MAbs provided protection in a murine model of pneumonia during neutropenia (28). A DNA vaccine encoding recombinant type a or type b P. aeruginosa flagellin also induced protective immunity against lethal P. aeruginosa lung infection (33), although this study curiously found better heterologous protection than homologous protection when DNA encoding wild-type flagellin was incorporated into the vaccine. A fusion protein of outer membrane protein F (OprF) residues 311 to 341, mature OprI residues 21 to 83, and flagellins a and b (termed OprF311-341-OprI-flagellins) generated significant immune responses in mice and promoted enhanced clearance of strain PA01 in a pulmonary challenge model (42).…”
mentioning
confidence: 99%